Lower limb force, power and performance in skateboarding: an exploratory study - Candotti, C. T.; Fagundes Loss, J.; Esteves Silva, R.; de Oliveira Melo, M.; Barreto Teixeira, R.; Becker Delwing, G.; Noll, M. (Revista Brasileira de Ciências do Esporte, 2012)
The purpose of this study was to identify the relationship between the height reached when performing the Ollie maneuver and the muscle force and power of the lower limbs required by beginner level skateboarders. Ten practitioners of Street category, with at least two years experience and who participate in competitions in Beginner, Amateur II or Amateur I categories were submitted to three tests: (1) maximal voluntary contraction of the knee and hip extensor muscles; (2) vertical jump tests, Counter Movement Jump (CJ) and Squat Jump (SJ); and (3) the maximum height achieved during the Ollie maneuver. The results demonstrate that the variance of the Ollie maneuver (p<0.05) is explained by the power estimated with the CJ (76.3%); and the maximal force of the knee extensor muscle (50.6%). These results suggest that the variable power is strongly associated with the performance of the Ollie maneuver.